Homem ou cidadão: Dificuldades da proposta pedagógico-política de Rousseau - QUEIROZ, Fabricio David de (2012)
To develop this dissertation we chose to follow the thought of Rousseau, gathers the educational theme and the political theme so arranged as to investigate the construction of a possible proposal of formation of the human for the life in society. From the beginning, we encounter the disjunctive presented by Rousseau in Emile that sets the tone of the problem to be developed in our research: "make a man or a citizen?" (2004, p. 11). This disjunctive introduces a series of difficulties to be faced along this research and can be summarized in the relationship that Rousseau established between nature and society. In the first chapter we will make an analysis of the figure of the natural man found both in the natural state of isolation, discussed under the light of the Discourse about the origin and the fundamentals of the inequality among men, as in the state of society, under the light of the Emile. From these works we hope to introduce the concept of man prepared by Geneva philosopher through by the original strokes and own of the humanity that, hypothetically, have not been disfigured by corrupt society that he had in front his eyes, the one where no one could find neither men nor citizens. Our purpose is to highlight that the natural man gathers around itself the qualities necessary for a full and happy life, marked above all by the natural freedom and equality among men; what gives it a higher life condition than civil man found in the corrupted society. Rousseau is very critical to political and moral corruption of modern society, placed that considers as degeneration or defacement of the human, as presented in its analysis of the statue of Glaucus. In order to deepen this discussion, the second chapter strives to theorize about the figure of the citizen discussing, fundamentally, the conditions of legitimacy of the social and political life as opposed to bourgeois figure, which represents the degeneration of man in the civil state. Taking as a basis for examining the Social Contract, or principles of political right, we will bring to the stage of the civil society the rightful citizen, saved from possible corruption process that is exposed when unsatisfactory led to civil status. Between the natural man and the civil man, there are discontinuities to be clarified so that we can comply with the purpose‟s Rousseau who, in our opinion, is to form the citizen in accordance with the formation of man. The task of forming not from the most simple, takes into account transforming human nature to make the man, that is a whole in itself, a citizen, which is part of a larger whole. Such a venture competes to education in order to make of the man a being moral and free, and at the same time integrated into the body politic and committed to its laws, it is up to the legal sphere to bring political freedom and equality once enjoyed in the state of nature. Finish this dissertation showing our understanding about what we consider to be an important contribution of the Rousseau's pedagogical-political thought: that nature and society can be understood, according to Rousseau‟s point of view, as solidarity instances that compose the man in its fullness and authenticity, lifting it out to civil condition in the figure of legitimate citizen.